Duels and the roots of violence in Missouri - Steward, Dick, 1942- (University of Missouri Press, 2000)
In early-nineteenth-century Missouri, the duel was a rite of passage for many young gentlemen seeking prestige and power. In time, however, social groups outside the ruling class engaged in a variety of violent acts and symbolic challenges under the rubric of the code duello. In Duels and the Roots of Violence in Missouri, Dick Steward takes an in-depth look at the evolution of dueling, tracing the origins, course, consequences, and ultimate demise of one of the most deadly art forms in Missouri history. By focusing on the history of dueling in Missouri, Steward details an important part of our culture and the long-reaching impact this form of violence has played in our society.